2001
DOI: 10.1103/physreva.63.023602
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein condensation in trapped bosons: A variational Monte Carlo analysis

Abstract: Several properties of trapped hard sphere bosons are evaluated using variational Monte Carlo techniques. A trial wave function composed of a renormalized single particle Gaussian and a hard sphere Jastrow function for pair correlations is used to study the sensitivity of condensate and noncondensate properties to the hard sphere radius and the number of particles. Special attention is given to diagonalizing the one body density matrix and obtaining the corresponding single particle natural orbitals and their o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(119 citation statements)
references
References 28 publications
6
109
4
Order By: Relevance
“…This appendix discusses the determination of various observables through the Monte Carlo sampling of the wave function ψ tot . Although our approach follows standard procedures [49,69,75], we find it useful to summarize a few key results in this appendix for completeness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appendix discusses the determination of various observables through the Monte Carlo sampling of the wave function ψ tot . Although our approach follows standard procedures [49,69,75], we find it useful to summarize a few key results in this appendix for completeness.…”
Section: Discussionmentioning
confidence: 99%
“…The density matrices not only lead to a practical route to determine the momentum distributions associated with the spin-up and spin-down atoms, but also serve to quantify the non-local correlations of the system. For example, for trapped single-species Bose gases, an eigen value of the one-body density matrix of the order of 1 signals a large condensate fraction [49,71,73,74]. The situation is different for two-component fermions [72,73].…”
Section: B Stochastic Variational Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic density in the trap is n ≃ 10 12 − 10 14 atoms/cm 3 giving an inter-atomic distance l = V A 1/3 ≃ 10 4Å [18]. In this case, the effective atomic size is small compared both to the trap size and to the inter-atomic distance ensuring the diluteness of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…Seventy years later, in a remarkable experiment, Anderson et al [9] have cooled magnetically trapped 87 Rb gas to nanokelvin temperatures, and observed the BEC. This discovery has generated a huge amount of theoretical investigations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%